Adult attachment, cultural orientation, and well-being in Greece - Kafetsios, Konstantinos; Kateri, Evangelia (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Social bonds and relationships are important determinants of well-being and happiness. Peoples’ propensities for relating to individual and cultural levels can partially account for variations in well-being in different cultures. The present paper examined how adult attachment orientations, a seminal aspect of relating, and independent and interdependent self-construal, a cultural category of social relations, interrelate at an individual level to explain well-being in Greece. In a large-scale community study state secure attachment and independent and interdependent cultural orientations were all positively associated with well-being. As expected, the two relating constructs intersected so that higher interdependence was associated with higher anxiety and lower avoidance in line with expectations. Importantly, the interaction between interdependence and anxious attachment accounted for an additional part of the variance in well-being: participants higher in anxiety and interdependence had higher well-being whereas the inverse was true for participants higher in anxiety and independence. These results point to culture-specific patterns in how central relating schemas contribute to well-being[1].